Video object segmentation by 2-D mesh-based motion analysis and morphological filtering - WANG Yu-jian; GAO Jian-po; WU Zhen-yang (Tongxin xuebao)
A new temporal-spatial video object segmentation algorithm was proposed.This algorithm was based on 2-D mesh-based motion analysis and an improved spatial automatic segmenting strategy of morphological filtering.Firstly,higher order statistics was used for motion analysis of the 2-D mesh representation.After post-processing,relatively fine motion detection mask was quickly obtained.Then a novel watershed segmenting strategy based on alternating sequential filtering by reconstruction and adaptive threshold was applied to get the accurate boundary of the foreground object.Fi-nally,the video object was effectively extracted by fusing the temporal and spatial segmentation via region-based method.Experimental results indicate that the proposed algorithm assimilates the advantages of 2-D mesh-based algorithms and pixel-based algorithms,and achieves satisfactory subject and object performance.